Systematics and biogeography of forest snails, chondrocyclus (mollusca: gastropoda: caenogastropoda: cyclophoridae) in Southern Africa - Cole, Mary Louise (Rhodes University, Faculty of Science, Botany Department, 2017)
This study presents a molecular phylogeny and systematic revision of Chondrocyclus, the major South African group of the large family of operculate terrestrial molluscs, the Cyclophoridae. Chondrocyclus snails are small gastropods found in forest and moist thicket throughout South Africa. This is the first detailed systematic treatment of a group of Cyclophoridae in mainland Africa and the first to provide molecular data. This study complements regional studies on the systematics of the family in Asia and provides comparative data for studies of higher level relationships within the Cyclophoridae. Phylogenetic reconstruction by BI and ML methods of combined and single gene datasets of 16S and CO 1 all showed Chondrocyclus to be monophyletic and recovered five well-supported clades that corresponded to groups of populations identifiable on the basis of combinations of morphological characters. Species were diagnosed morphologically and were shown to be genetically distinct lineages. Informative morphological features include shell dimensions, protoconch, periostracum, operculum, radula and penis. Two species in Afromontane regions of Zimbabwe and Malawi respectively are excluded from Chondrocyclus based on morphology and tentatively placed in Cyathopoma. Diversity recognised within the genus more than doubled, from a previous seven South African species to seventeen. Re-descriptions of established species and descriptions of new species are provided, together with photographs of morphological characteristics. New taxon names and nomenclatural acts within it are disclaimed and are therefore not available in the sense of the International Code of Zoological Nomenclature until validly published elsewhere. Several cryptic species within previously widespread "species" and unrecorded narrowly endemic species were documented. The clade consisting of populations of "Chondrocyclus isipingoensis" , now considered to be a species complex, was sister to a group containing the other four clades. The "Isipingoensis" clade occurs widely in Afromontane regions, along the Great Escarpment, and on the south-east coast. The other four clades occur from Zululand to the Cape Peninsula with a pattern of east-west lineage turnover. The biogeography of Chondrocyclus is interpreted by comparison with concordant patterns in other terrestrial molluscs and unrelated taxa with poor dispersal ability. This study complements other research on composition, spatial distribution and phylogenetic diversity of low-vagility invertebrates and expands the data available for biodiversity conservation in South Africa.
Keywords: Chondrocyclus; Mollusks -- South Africa; Cyclophoridae -- South Africa